The institutional imperative the politics of equitable development in Southeast Asia - Kuhonta, Erik Martinez 1973- (Studies of the Walter H. Shorenstein Asia-Pacific Research Center, 2011)
This book is a comparative-historical study of the politics of equitable development in Southeast Asia and the role of political institutions in addressing structural inequalities